Electronic microscopy of eggs as a taxonomic parameter (1995)
The egg surface structure has been used to provide more detailed observations on the eggs of Phlebotomine sand fly species Such knowledge could be of practical value in the taxonomical separation of closely related species (Lindquist 1936, Barreto 1941 Addıs 1945 Sherlock 1957. Chaniotis and Anderson 1964. Ward and Ready 1975 Zimmerman et al 1977: Endrıs et al 1987 Feliciangeli et al 1993) The form of the sculpturing of insect eggs is believed to be influenced by environmental conditions in the microhabitat where the eggs are laid (Hinton. 1960 and 1968) This factor must be of significance to examine the existence of intraspecific variation related to breeding sites